Securing Electricity Supply in the Cyber Age Exploring the Risks of Information and Communication Technology in Tomorrow's Electricity Infrastructure - Lukszo, Zofia; Deconinck, Geert; Weijnen, Margot P. C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
The electricity infrastructure is one of society$1 (Bs most critical infrastructures. The complexity of the electricity infrastructure system is increasing quickly, due to the increasing intensity of trade within and between electricity systems, the associated market restructuring and an increasing share of decentralized generation. At the same time, there is a shift in public goals towards low-carbon and sustainable power generation. This requires a drastic transformation of the industry. Increasingly, ICT is being depended upon for managing this infrastructure, for technical control and operation as well as for facilitating markets. A recent example is demand-side management, which requires detailed metering of consumption and decentralized electricity generation. The mutual dependence of the electricity and the ICT infrastructures raises challenging questions in the areas of dependability, security and resilience. Examples include vulnerability to (cyber) attacks, avoiding and repairing technical failures and protecting data confidentiality, while guaranteeing accessibility. Therefore, better models and methods for protection against exploits of system vulnerabilities, whether accidental or intentional such as in cyber attacks, are called for. These problems were addressed at an advanced research workshop, titled "Electricity security in the cyber age: Managing the increasing dependence of the electricity infrastructure on ICT", which was organized in the Netherlands in May 2009. The objective of the workshop was to contribute to the security of current and future electricity infrastructures by analyzing the risks that are caused by the increasing reliance upon ICT and investigating options for managing these risks. This book presents the contributions to the workshop by distinguished invited keynote speakers and participants from the international scientific and industrial community.s
Keywords: Engineering; Energy policy; Energy and state; Electric power production; Quality control; Reliability; Industrial safety; Electrical engineering; Electronic circuits; Economic policy; Engineering; Energy Technology; Communications Engineering, Networks; Quality Control, Reliability, Safety and Risk; Circuits and Systems; Energy Policy, Economics and Management; Economic Policy; Electronic books